Nature’s Queer Performativity* - Karen Barad (The Royal Danish Library, 2012)
In this article, Karen Barad entertains the possibility of the queerness of one of the most pervasive of all critters – atoms. These “ultraqueer” critters with their quantum quotidian qualities queer queerness itself in their radically deconstructive ways of being. Given that queer is a radical questioning of identity and binaries, including the nature/culture binary, this article aims to show that all sorts of seeming impossibilities are indeed possible, including the queerness of causality, matter, space, and time. What if queerness were understood to reside not in the breech of nature/culture, per se, but in the very  nature of spacetimemattering, Barad asks. This article also considers questions of ethics and justice, and in particular, examines the ways in which moralism insists on having its way with the nature/culture divide. Barad argues that moralism, feeds off of human exceptionalism, and, in particular, human superiority and causes injury to humans and nonhumans alike, is a genetic carrier of genocidal hatred, and undermines ecologies of diversity necessary for flourishing.